Palladium-catalyzed direct alkynylation of thiophenes with halosilylacetylenes. (16th March 2021) - Kato, Hayate; Tsukada, Naofumi
Graphical abstract: Highlights: Palladium catalyzed alkynylation of thiophenes with halosilylacetylenes. Regioselective alkynylation of thiophenes. Transformation of a silylalkynyl substituent on thiophene. Abstract: Silylethynylthiophenes were obtained from palladium-catalyzed alkynylation of various thiophenes with 1-halo-2-silylacetylenes. The α-position of thiophenes was alkynylated with high regioselectivity. The terminal silyl groups of products could be replaced by several functional groups.